Cord blood transplantation for adult lymphoid neoplasms in Europe and Japan - Watanabe, Mizuki; Kanda, Junya; Volt, Fernanda; Ruggeri, Annalisa; Suzuki, Ritsuro; Rafii-Elayoubi, Hanadi; Kimura, Fumihiko; Cappelli, Barbara; Kondo, Eisei; Scigliuolo, Graziana Maria; Takahashi, Satoshi; Kenzey, Chantal; et al. (Blood advances, 2024)
With the aim of identifying the different characteristics and prognostic factors of cord blood transplantation (CBT) in adult patients with lymphoid neoplasms in Europe and Japan, we conducted a collaborative study between European and Japanese registries. Patients aged 18-75 years receiving their first CBT (Europe: single CBT, n=192; double CBT, n=304; Japan: single CBT, n=1150) in 2000-2017 were analyzed. The number of patients with Hodgkin's lymphoma was higher in Europe (26% vs 5%) while that with mature T/NK-cell neoplasms was higher in Japan (20% vs 35%). The Japanese cohort comprised more elderly patients (>=50) (59% vs 39%) with higher refined disease risk index (rDRI) (high-very high: 49% vs 14%). High-very high rDRI (vs. low rDRI) was associated with inferior OS in common (Europe: HR 1.87 p=0.001; Japan: HR 2.34, p<0.001) with higher progression/relapse risks (Europe: HR 2.04, p=0.007; Japan: HR 2.96, p<0.001). Total body irradiation (TBI)-containing conditioning regimens contributed to superior OS both in Europe (vs TBI-RIC, non TBI-RIC: HR 1.93, p<0.001; non TBI-MAC: HR 1.90, p=0.003) and in Japan (non TBI-RIC: HR 1.71, p<0.001; non TBI-MAC: HR 1.50, p=0.007). The impact of HLA mismatches (>=2) on OS differed (Europe: HR 1.52, p=0.007; Japan: HR 1.18, p=0.107). Despite the different patient-disease-transplant characteristics, poor survival of patients receiving CBT for lymphoid neoplasms, especially in those with high rDRI was observed in both registries. The different impact of HLA mismatches on survival in the two registries calls attention to the fundamental differences among these populations. TBI should be considered in conditioning regimens.